7 - Fonds miniers volontaires et développement communautaire au Sénégal : quelle place et quels rôles pour la démocratie délibérative et participative ? Bakary DOUCOURÉ - Bakary DOUCOURÉ, (African Sociological Review, 2021)
This article focuses on the Social and Environmental Investment Fund (FISE) of the gold mining company Petowal Mining Company (PMC SA) based in Senegal. It addresses the democratic issue by analyzing the place and roles of deliberative and participatory processes in a context of mining extractivism and community development. It shows the limits of voluntary mining funds to stimulate effective and sustainable development at the local level, due in particular to the shortcomings related to the application of deliberative and participatory processes in the establishment of these funds and the resulting projects / actions.